Assesment of palliative care in lung cancer in Turkey (ASPECT study) - Bulbul, Yilmaz; Ozlu, Tevfik; Arinc, Sibel; Ozyurek, Berna A.; Gunbatar, Hulya; Senturk, Aysegul; Talay, Fahrettin (European Respiratory Soc Journals Ltd, 2015)
[Abstract Not Available]
Keywords: Lung cancer / Oncology; Neoplastic diseases; Palliative care